Methamphetamine Enhances HIV-1 Replication in CD4+ T-Cells via a Novel IL-1β Auto-Regulatory Loop - Lawson, Kaycie S.; Prasad, Anil; Groopman, Jerome E. (Frontiers in Immunology, 2020)
Methamphetamine (Meth) abuse is a worldwide public health problem and contributes to HIV-1 pathobiology and poor adherence to anti-retroviral therapies. Specifically, Meth is posited to alter molecular mechanisms to provide a more conducive environment for HIV-1 replication and spread. Enhanced expression of inflammatory cytokines, such as Interleukin-1β (IL-1β), has been shown to be important for HIV-1 pathobiology. In addition, microRNAs (miRNAs) play integral roles in fine-tuning the innate immune response. Notably, the effects of Meth abuse on miRNA expression are largely unknown. We studied the effects of Meth on IL-1β and miR-146a, a well-characterized member of the innate immune signaling network. We found that Meth induces miR-146a and triggers an IL-1β auto-regulatory loop to modulate innate immune signaling in CD4 + T-cells. We also found that Meth enhances HIV-1 replication via IL-1 signaling. Our results indicate that Meth activates an IL-1β feedback loop to alter innate immune pathways and favor HIV-1 replication. These observations offer a framework for designing targeted therapies in HIV-infected, Meth using hosts.